2021
DOI: 10.3171/case21131
|View full text |Cite
|
Sign up to set email alerts
|

A focal brain-cooling device as an alternative to electrical stimulation for language mapping during awake craniotomy: patient series

Abstract: BACKGROUND Functional mapping in awake craniotomy has the potential risk of electrical stimulation-related seizure. The authors have developed a novel mapping technique using a brain-cooling device. The cooling probe is cylindrical in shape with a thermoelectric cooling plate (10 × 10 mm) at the bottom. A proportional integration and differentiation-controlled system adjusts the temperature accurately (Japan patent no. P5688666). The authors used it in two patients with glioblastoma. Broca’s area was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…However, intraoperative focal cooling of specific brain regions during performance of vocal sequences in awake neurological patients was found, in of itself, to enable functional segregation of cortical areas underpinning speech timing and articulation, and aid avoidance of critical speech centres during surgical resection 39 . It has also recently been reported that intraoperative direct focal cooling of the brain using a similar approach as in our study (i.e., a PID-controlled system) enabled language mapping through monitoring of thermal changes due to functional hyperaemia 40 (and see Figure 1E in the current manuscript). Since intrinsic optical imaging spectroscopy (OIS) methods, identical to those used here, have also been successfully implemented in the operating theatre [41][42][43][44] , and given our observation of a "deoxy-dip" during sensory processing at cool cortical temperatures that is spatially localised to site of neuronal activation (see above), it is thus tempting to speculate that the combination of focal cooling and OIS intra-operatively would not only reduce the risk of epileptiform activity during associated functional mapping, but also improve mapping accuracy.…”
Section: Discussionsupporting
confidence: 56%
“…However, intraoperative focal cooling of specific brain regions during performance of vocal sequences in awake neurological patients was found, in of itself, to enable functional segregation of cortical areas underpinning speech timing and articulation, and aid avoidance of critical speech centres during surgical resection 39 . It has also recently been reported that intraoperative direct focal cooling of the brain using a similar approach as in our study (i.e., a PID-controlled system) enabled language mapping through monitoring of thermal changes due to functional hyperaemia 40 (and see Figure 1E in the current manuscript). Since intrinsic optical imaging spectroscopy (OIS) methods, identical to those used here, have also been successfully implemented in the operating theatre [41][42][43][44] , and given our observation of a "deoxy-dip" during sensory processing at cool cortical temperatures that is spatially localised to site of neuronal activation (see above), it is thus tempting to speculate that the combination of focal cooling and OIS intra-operatively would not only reduce the risk of epileptiform activity during associated functional mapping, but also improve mapping accuracy.…”
Section: Discussionsupporting
confidence: 56%
“…the assembly of speech elements into meaningful sentences) 37,38 . This is further supported by studies using cortical cooling showing that silencing the ventral precentral gyrus or premotor cortex impacts the quality of speech 39,40 , while cooling pars opercularis and pars triangularis of Broca's area stretches the timing of speech 40 . This body of evidence suggests that the neural dynamics of Broca's area may likely play an important role in the encoding of speech sequences.…”
Section: Introductionmentioning
confidence: 75%
“… Language + Motor Verbal tasks + Motor movements Motor Opening + closing hand Flexion + tension foot Complex movement such as screwing a nut Visuospatial Line bisection task Object naming in opposite quadrants Social cognition Emotion recognition task Executive function Go/No-go task Working Memory Memorize stimuli, then distraction: is this stimuli the same as previous or not? Calculation Calculation [ 178 ] Language Picture naming Nonverbal semantic association test ( PPTT ) Social cognition Reading the Mind in the Eyes Test [ 179 ] Language Counting Object picture-naming task ( DO80 ) Semantic association task Language + Motor Counting/ DO80 + Contralateral movement [ 180 ] Language Number counting Picture naming task Verbal semantic association task (PPTT) Motor Upper limb movements Visuospatial Line bisection task [ 181 ] Language Counting Picture naming [ 182 ] Language Counting Motor Finger grasping Sticking out tongue Moving the fingers [ 183 ] Language Naming items Motor Finger tapping task [ 184 ] Language Picture naming Word reading Spontaneous speech [ 185 ] Language Free conversation Picture naming Responsive naming [ 186 ] ...…”
Section: Resultsmentioning
confidence: 99%